The Continued Importance of Open Educational Resources (OER) - Simon Paul Atkinson; Alison Fields (Flexible Learning Association of New Zealand, 2023)
The longevity of educational delivery using Open Educational Resources (OER) and Open Education Practices (OEP) highlights the ongoing importance of open resources. Open Educational Resources are teaching and learning materials that are created and licensed as either in the public domain or as free, able to be shared, and able to be modified. During the massive uptake of online learning practices during the COVID-19 pandemic, the uptake of OER resources and practices showed only modest growth. Now that the pressure for delivering Emergency Remote Teaching (ERT) is off, it's time to look again at OER as a cost-effective and sustainable way to resource and deliver education practices. McGreal, Macintosh, and Lane continue the OER story from previous articles in this journal, looking specifically at OER-based online micro-courses supporting the UNESCO Strategic Development Goal 4: Education for All. The issue is rounded off with four articles highlighting other areas of flexible learning including learning support, learning satisfaction, learner retention, and learner experience.